Childhood cancer incidence in a cohort of twin babies. - Murphy, M; Whiteman, D; Hey, K; Griffith, M; Gill, L; Goldacre, M; Vincent, T; Bunch, K (2001)
We studied childhood cancer incidence in a population-based twin cohort using record linkage to the National Registry of Childhood Tumours. After correcting for mortality, an incidence deficit was observed (Standardized Incidence Ratio (SIR) 79; 95% Confidence Interval (CI) 39-120). Pooled analysis with data from published cohort studies indicates a similar significant incidence reduction (SIR 81, 95% CI 67-96). Further studies are warranted.